STRENGTHENING NASIONALISM CHARACTER THROUGH LITERARY WORKS - Krishandini Krishandini; Endang Sri Wahyuni; Defina Defina (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
There are a few worries from parents and Indonesian linguists in Indonesia when they notice that there are so many young people speak foreign language (especially English) that it will eliminate Indonesian language permanently. In addition, parents and linguists worry that young Indonesian people will loose their nationalism character. According to Whorf (1952), the linguistic system of language is not merely a reproducing instrument for voicing ideas but rather is itself the shaper of ideas, the program and guide for the individual’s mental activity. Whorf’s statement will strengthen the worry of loosing nationalism character because this will give opportunity to people to make new language replacing Indonesian language. This happens because young people always switch back and forth between Indonesian and English formally and informally. If this keeps continuing, young Indonesian people will forget their culture for good. It is, therefore, the Indonesian goverment has given first language since they were in elementary level until university level in order to overcome the lose of culture. However, how the first language education is given to them to build nationalism charcter is effective. Thus, Is it true that the character of nationalism young Indonesian people has faded? For example, in this paper, the writers will describe the IPB (Bogor Agriculture University) students expression of their nationalism. So, in this paper, the writers will show some poems taken from IPB students to indicate their nationalism character. Keywords: nasionalism, character, students